Tiga Kearifan Lokal Masyarakat Pesisir Pantai Selatan Cilacap Sebagai Upaya Mitigasi Bencana Gempa Bumi dan Tsunami - Ahmad Dahlan; Suwarno Suwarno (Proceedings Series on Social Sciences & Humanities, 2022)
This article aims to examine the local wisdom of the south coast community of Cilacap Regency as one of the efforts in Disaster Risk Reduction (DRR). This study used descriptive qualitative method. Data collection is done through documentation. Furthermore, the data were analyzed qualitatively, through data reduction, data presentation, and drawing conclusions. The results of the study show that the Cilacap people still hold firmly to their beliefs and customs which are reflected in their daily activities. This can also be traced historically. The local wisdom of the Cilacap people related to earthquake and tsunami disaster mitigation is reflected in (1) Belief in the existence of Nyi Roro Kidul who is the ruler of the south coast which is believed to have occurred in large waves. From here, the community learns about preparedness for a tsunami that can occur at any time. 2) the sea alms tradition, namely by holding a ritual of throwing offerings into the sea as a symbol of gratitude for the blessings of marine products obtained as well as prayers and hopes for safety. (3) Mount Selok which is considered to have a blessing for those who believe in it so that the community protects it as a tangible manifestation of ecosystem conservation and is a protective fence for the land from the tsunami. With these three local wisdoms, people from generation to generation have had the knowledge to be prepared, protect the environment and be grateful for the blessings that come from nature while maintaining its sustainability. namely by holding a ritual of throwing offerings into the sea as a symbol of gratitude for the blessings of the marine products obtained as well as prayers and hopes for safety. (3) Mount Selok which is considered to have a blessing for those who believe in it so that the community protects it as a tangible manifestation of ecosystem conservation and is a protective fence for the land from the tsunami. With these three local wisdoms, people from generation to generation have had the knowledge to be prepared, protect the environment and be grateful for the blessings that come from nature while maintaining its sustainability. namely by holding a ritual offering offerings to the sea as a symbol of gratitude for the blessings of the marine products obtained as well as prayers and hopes for safety. (3) Mount Selok which is considered to have a blessing for those who believe in it so that the community protects it as a tangible manifestation of ecosystem conservation and is a protective fence for the land from the tsunami. With these three local wisdoms, people from generation to generation have had the knowledge to be prepared, protect the environment and be grateful for the blessings that come from nature while maintaining its sustainability. (3) Mount Selok which is considered to have a blessing for those who believe in it so that the community protects it as a tangible manifestation of ecosystem conservation and is a protective fence for the land from the tsunami. With these three local wisdoms, people from generation to generation have had the knowledge to be prepared, protect the environment and be grateful for the blessings that come from nature while maintaining its sustainability. (3) Mount Selok which is considered to have a blessing for those who believe in it so that the community protects it as a tangible manifestation of ecosystem conservation and is a protective fence for the land from the tsunami. With these three local wisdoms, people from generation to generation have had the knowledge to be prepared, protect the environment and be grateful for the blessings that come from nature while maintaining its sustainability.